2013
DOI: 10.2174/1574886311308020004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adverse Drug Reactions Between High- and Standard- Dose Trimethoprim-Sulfamethoxazole in the Ambulatory Setting

Abstract: ADRs such as hyperkalemia are more likely to be associated with the use of high-dose TMP-SMX in the ambulatory setting. Clinicians should use caution when initiating high-dose TMP-SMX and consider laboratory monitoring in patients of advanced age or those receiving concomitant ACE inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
2
23
2
Order By: Relevance
“…It was thought that all Nocardia strains are susceptible to these drugs (334); however, this is not the case, and susceptibility testing should be performed before starting the treatment (335), given that resistance is specie specific (336,337). Besides, some people are allergic to TMP-SMX, which is sometimes observed after treatment starts with the additional risk that this brings for the patient (338). The standards dictate that for cutaneous disease, TMP-SMX should be administered for 1-3 months, for pulmonary disease during 6-12 months, and for disseminated, especially CNS infection, it should be of 12 months sometimes, even more, depending on the progress of the disease (339).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…It was thought that all Nocardia strains are susceptible to these drugs (334); however, this is not the case, and susceptibility testing should be performed before starting the treatment (335), given that resistance is specie specific (336,337). Besides, some people are allergic to TMP-SMX, which is sometimes observed after treatment starts with the additional risk that this brings for the patient (338). The standards dictate that for cutaneous disease, TMP-SMX should be administered for 1-3 months, for pulmonary disease during 6-12 months, and for disseminated, especially CNS infection, it should be of 12 months sometimes, even more, depending on the progress of the disease (339).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…In this exploratory study, rates of adverse event was higher than reported previously to the combination of sulfamethoxazole and trimethoprim [9]; however, these results should be taken carefully interpreted because this work is only designed to obtain a sample size for a further study.…”
Section: Discussionmentioning
confidence: 67%
“…The result of the calculation is 48.4 patients. The premise of a probability adverse-drug reaction of 6% was obtained in a previous article by Nguyen et al [9], describing an adverse drug reaction rate of 9% in a cohort of patients treated with high and standard doses of the combination of sulfamethoxazole and trimethoprim where the frequency of adverse reactions for standard dose was 5.1%.…”
Section: Methodsmentioning
confidence: 99%
“…Newer fluoroquinolones, minocycline or tigecycline might be future alternatives to combat emerging TMP/ SMX resistance; however, the selection of resistant S. maltophilia strains with the use of quinolones remains a concern [2]. The administration of TMP/SMX can be associated with adverse events such as neutropaenia, hepatopathy or decreased tubular secretion of creatinine and also with more uncommon severe skin diseases such as Stevens-Johnson syndrome or with central nervous system side effects [3]. However, the complication rate in this study was low.…”
Section: Discussionmentioning
confidence: 99%
“…A high dose of TMP (15 mg/kg/day) is generally recommended to reduce the risk of emerging resistance to TMP/SMX [1]. However, allergic reactions and toxicities related to the administration of TMP/SMX in patients limit the use of this drug in clinical practice [3]. Fluoroquinolones are an alternative option for treatment, if the pathogen is shown to be susceptible to the specific antimicrobial in vitro [1,2].…”
Section: Introductionmentioning
confidence: 99%